Online monitoring and active control of alignment errors in a tiled grating assembly using single wedge plate. (February 2023) - Daiya, D.; Patidar, R.K.; Moorti, A.; Benerji, N.S.; Bindra, K.S.
Highlights: Simple and sensitive interferometric method for coherent alignment of tiled grating assembly with enhanced measurement sensitivity and reduced hardware for online monitoring and active alignment error correction. A small aperture single wedge plate has been used for generating interferogram for both the reflected and diffracted beams. Simultaneous recording of both the interferogram using single CCD camera. Online monitoring and active locking of all tiling alignment errors has been presented within the range of ± 0.5 µrad for angular errors and ±50 nm for translation errors. Abstract: With reference to application in chirped pulse amplification (CPA) based high-energy, ultra-short laser systems, online monitoring of alignment errors and active coherent locking of gratings in a tiled grating assembly (TGA) consisting of two gratings, each of size 140 mm x 120 mm and groove density 1740 grooves/mm, is presented. All the tiling alignment errors present in the TGA have been monitored simultaneously using a single wedge plate based lateral shearing interferometry and corrected using piezo motor driven 6-axis aligner stage. As a novelty, to have further advantages in the wedge plate based method for TGA alignment, the He-Ne laser beam diffracted/ reflected from the TGA has been folded back towards the source, which facilitated measurement sensitivity enhancement by a factor of two, and also generation and simultaneously capturing of both reflected and diffracted beam's interferograms using comparatively smaller dimension single wedge plate and CCD camera. The angular and translational alignment errors of the TGA have been actively locked in the range of ± 0.5 µrad and ± 50 nm respectively.